(12+2x)(26+2x)=1472

Simple and best practice solution for (12+2x)(26+2x)=1472 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (12+2x)(26+2x)=1472 equation:



(12+2x)(26+2x)=1472
We move all terms to the left:
(12+2x)(26+2x)-(1472)=0
We add all the numbers together, and all the variables
(2x+12)(2x+26)-1472=0
We multiply parentheses ..
(+4x^2+52x+24x+312)-1472=0
We get rid of parentheses
4x^2+52x+24x+312-1472=0
We add all the numbers together, and all the variables
4x^2+76x-1160=0
a = 4; b = 76; c = -1160;
Δ = b2-4ac
Δ = 762-4·4·(-1160)
Δ = 24336
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{24336}=156$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(76)-156}{2*4}=\frac{-232}{8} =-29 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(76)+156}{2*4}=\frac{80}{8} =10 $

See similar equations:

| (12+2x)(26+2x)=147 | | x-−5=4x+10 | | (16+2x)(22+2x)=832 | | 8^2x-1=32^2x+1 | | -4x+10=2x-12 | | 14×30=2x | | 2x-7x+9=-6 | | 5^x+1=36 | | 3x+2+x=-x+10+x | | 2y-3(26-3)+2=31 | | 2y-3(26-3)+2=3@ | | 18y^2+51y-42=0 | | 18x^2+51x-42=0 | | x^2/8+x/2 =10 | | 8.1p+2.3=5.1p-3.1 | | F(t)=-2t^2+22t | | 12y^2=+19y-18 | | 8x=12x+3 | | 11b+70=4 | | 7x2+7x+-8=0 | | 4x=12*7 | | 3x+6=51−2x | | 49+8x=x | | 8x+7=11x+1 | | 3y-4=8-y | | 7x+x+78=180 | | x^2+4x=14x | | 6*6x=x | | 8m+7=86 | | 2x^2−40x=172 | | 2(8x-5)=-4x | | 4^(2x-1)=8^(2x) |

Equations solver categories